Assessment of trace metals contamination in surficial sediments along Lebanese Coastal Zone. (August 2018) - Merhaby, Dima; Ouddane, Baghdad; Net, Sopheak; Halwani, Jalal
Abstract: A Characterization and assessment study was conducted for trace metals pollution in surface sediments at six sites including harbors, bays and river input along Lebanese coast (LCZ). A particular attention was given to Tripoli Port in order to identify the main sources of trace metals pollution inside this harbor. Total metals concentrations were compared with those reported for the shale. The results revealed that trace metals (Cd, Pb, Zn, and Cr) contamination was significantly localized at Beirut Port, which is classified as the most highly polluted site. At Tripoli Port site, metals contamination was classified as moderate; it is affected by shipping, ship maintenance activities and sewage outfall. According to the SQGs guideline, the biological adverse effect of Cd, Pb and Zn were expected to occur frequently at Beirut Port. The results obtained would be helpful in developing more effective harbor management strategies to control and monitor the metal discharges. Graphical abstract: Unlabelled Image Highlights: Assess trace metal pollution in sediments of six hotspots sites along Lebanese coast Cd, Zn, Pb and Cr was the most abundant trace metals in studied sediments. Highest contamination is localized at Beirut Port. Biological adverse effect was expected between frequently to occasionally. Harbor management strategies to control the metal discharges are recommended.